International norms development and AI in the military domain - Tim Sweijs; Sofia Romansky (Centre for International Governance Innovation (CIGI), 2024)
The growing use of artificial intelligence (AI) in military applications has changed the way countries engage in war and in times of peace. With so many potential effects of military AI applications, both positive and negative, there is growing demand for international norms to govern their responsible use based on ethical and legal principles. While some argue that current international and human rights laws are sufficient, this paper makes the case for expanding norms to encompass the rapid growth of military AI use while looking at the challenges facing international norms development, current initiatives, and strengths and weaknesses in the normative landscape.
Keywords: 330